Can Operating Room Efficiency be Increased by Applying the Lean Six Sigma Models? - Michelin, Lorenzo; Ricci, Beatrice; Barbagallo, Venerando; Perger, Peter; Padovani, Emanuele; Giardina, Federico; Traina, Francesco; Campagna, Anselmo; Damen, Viola; Buccioli, Matteo (Archives of Clinical and Medical Case Reports, 2021)
Executive summary This study was inspired by Operating Room efficiency studies and the growing use of management models established in the manufacturing sector, applied to the management of operating rooms. Furthermore, as these models are theoretical guidelines, the study will attempt to discuss their key concepts and application in the hospital sector. The objective of the study is to understand if and how management models have been useful to improve the efficiency of operating theatres. Since operating theatres are a sector that mobilizes large amounts of resources and can be considered the production line of the hospital, it is useful to apply new organizational models to increase performance. To this end, data concerning operating theatres before (2018) and after the reorganization (2019) have been compared, inspired by the concepts of efficiency studied by Macario, the monitored data have been calculated using performance indicators using time as the main measure. The hospital made an organizational change that led to reorganizing the OR schedule according to Lean Six Sigma management models. This has led to a change in the allocation of surgical sessions. In 2018 there was a prevalence of short OR (parallel) sessions in the mornings, while in 2019 a prevalence of (consecutive) sessions mornings and afternoons for the same surgical units. In 2019 an attempt was also made to group similar cases in the same session in order to standardize the process and reduce variability. The KPI values considered in the study show an improvement in performance and use of resources.